Young people's compliance with the Experience Sampling Method (ESM): Examining patterns, predictors and associations with well-being and mental health - Julius März; Lianne P. de Vries; Hanneke Scholten; Annabel Vreeker; Jeroen S. Legerstee; Loes Keijsers; Brenda W.J.H. Penninx; Manon H.J. Hillegers (Internet Interventions)
The Experience Sampling Method (ESM) can help young people gain insight into their fluctuating emotions through multiple daily surveys. This can act as an intervention to improve well-being and mental health. However, the effectiveness of ESM interventions is expected to depend on compliance, i.e., how often participants respond to these surveys. We aimed to understand compliance patterns among young people during an ESM-based intervention, explored predictors of these patterns, and examined if the intervention's impact on well-being and mental health varied with compliance levels.Dutch adolescents and young adults (N = 1139, 12–25 years, mean age = 17.67; 79 % female) completed baseline questionnaires, responded to five daily ESM surveys over three weeks using the Grow It! app, and completed follow-up questionnaires.Despite overall low compliance (mean compliance = 33.8 %), latent class growth analyses identified four compliance patterns: stable high (N = 176; M = 78.8 %), stable medium (N = 193; M = 50.1 %), high initial and decreasing (N = 272; M = 30.9 %), and low initial and decreasing (N = 498; M = 13.2 %). These patterns were not consistently associated with age, gender, education, baseline well-being, or depressive and anxiety symptoms, and did not influence the intervention's effect on well-being and mental health outcomes.We identified specific ESM compliance patterns among young people but found no clear predictors or outcomes of these patterns. To improve compliance and intervention effectiveness, future ESM interventions can potentially be enhanced by personalized designs, incorporating intrinsic and extrinsic motivators, and investigating situational factors and additional participant characteristics.